STEMFLOW, THROUGHFALL AND RAINWATER INTERCEPTION OF EIGHT INDONESIAN TREE SPECIES - Siti Sofiah; Soejono Soejono (SEAMEO BIOTROP, 2020)
Tree architecture affects how rainwater is partitioned into canopy interception, throughfall, and stemflow. The canopy shape and bark/leaf surface morphology influence the plants' ability to intercept and redistribute rainwater. Therefore, tree structure plays a key role in soil and water conservation, particularly in reducing erosion and runoff. This research was conducted to predict the most suitable tree species for soil and water conservation and recorded 32 rainfall events during the rainy season from January 2014 to March 2015 in Purwodadi–LIPI, Indonesia. The stemflow, throughfall, individual tree architectural characteristics, and leaf morphology were measured for eight selected local tree species, namely: Sterculia cordata, Aleurites moluccana, Buchanania arborescens, Calophyllum inophyllum, Dysoxylum gaudichaudianum, Peltophorum pterocarpum, Alstonia scholaris, and Pometia pinnata. The species that showed the greatest interception capacity was Aleurites moluccana, with 68.1% of rainfall intercepted. Special leaf characteristics (such as fine hairs), globose stems, and long, grooved bark likely contributed to a greater relative interception of rainwater compared to other species. The throughfall and stemflow of each species were closely correlated with rainfall amount but not with rainfall intensity.